Decisions About Turns in Multiparty Conversation: From Perception to Action - Bohus, Dan; Horvitz, Eric (2011)
We present a decision-theoretic approach for guiding turn taking in a spoken dialog system operating in multiparty settings. The proposed methodology couples inferences about multiparty conversational dynamics with assessed costs of different outcomes, to guide turn-taking decisions. Beyond considering uncertainties about outcomes arising from evidential reasoning about the state of a conversation, we endow the system with awareness and methods for handling uncertainties stemming from computational delays in its own perception and production. We illustrate via sample cases how the proposed approach makes decisions, and we investigate the behaviors of the proposed methods via a retrospective analysis on logs collected in a multiparty interaction study.